Activated sintering of ceramics on the basis of Al[2]O[3] - Matrenin S. V. Sergey Veniaminovich; Ovechkin B. B. Boris Borisovich; Zenin B. S. Boris Sergeevich; Tayukin R. V. (Materials and technologies new generations, 2015)
Title screen